Analysis of Fiscal Equalisation Funds and Local Financial Autonomy in West Tanjung Jabung Regency - Muhammad Teja; Zulfanetti; Jaya Kusuma Edy (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze the development of balancing funds, the structure of balancing funds, and the level of regional financial independence in Tanjung Jabung Barat Regency during the 2020 to 2024 period. This study uses a descriptive quantitative approach with secondary data obtained from the Regional Revenue and Expenditure Budget (APBD) Realization Report published by the Directorate General of Fiscal Balance (DJPK), Ministry of Finance of the Republic of Indonesia. The analytical methods used include development analysis, contribution analysis, and regional financial independence ratio analysis. The results show that balancing funds remain the main source of regional revenue, with an average contribution of 87% to total regional revenue. The structure of balancing funds is dominated by Revenue Sharing Funds (DBH) and General Allocation Funds (DAU), while the average regional financial independence ratio is only 8%, which is categorized as very low. These findings indicate that Tanjung Jabung Barat Regency still has a high level of dependence on central government transfers. Therefore, efforts are needed to optimize Regional Original Revenue (PAD) to increase fiscal capacity and strengthen regional financial independence.